Carven im Vergleich zur Skitechnik des sportlichen Skiläufers (Rennläufers) und des Freizeit- bzw. "Komfort-Skiläufers" - Kaiser, F. (Sportverletzung Sportschaden, 1997)
In skiing there is principally no difference between the operating mechanism of a ski-racer and a skier who masters the technic of carving. Both try to ski with as less sliding as possible. The pressure distribution on the ski in a curve is very important. Near the end of the curve the pressure on the edge of the ski must be increased through various methods, on the one hand to avoid sliding and on the other hand to prepare the next curve correctly. In mastering the necessary mechanism of movements, the carving with the more wasted skis will be easier, because it is not necessary to put as much pressure on the last section of the ski, as it is necessary with the original skies to have the same result. Therefore even the holiday-skier has the possibility with carving-skis to master the ski-technic of the ski-racer and to have the pleasure of carving instead of sliding.